Peranan Ombudsman dalam Pengawasan Penerimaan Peserta Didik Baru SMA Negeri di Kota Palembang Tahun Ajaran 2024/2025 - Gunawan, Astra; Salia, Erli; Djufri, Darmadi (Pamulang Law Review, 2025)
This study aims to analyze the role of the Ombudsman of the Republic of Indonesia, South Sumatra Representative Office, in supervising the implementation of New Student Admissions (PPDB) at public senior high schools in Palembang City for the 2024/2025 academic year, as well as identifying the obstacles encountered. The research method employed an empirical juridical approach with data collection techniques through interviews, document studies, and observation. The findings reveal that the Ombudsman plays a crucial role in ensuring that PPDB implementation complies with Minister of Education and Culture Regulation No. 1 of 2021 and the policies of the South Sumatra Provincial Education Office. The supervisory measures include preventive actions (preventing maladministration) and repressive actions (handling reports and investigations). The main challenges include limited resources, weak internal supervision, and interference from interested parties. The study concludes that Ombudsman oversight improves compliance with regulations but requires collaborative support from all stakeholders.